2004
DOI: 10.1002/adsc.200404018
|View full text |Cite
|
Sign up to set email alerts
|

Titanium‐Catalyzed Tandem Sulfoxidation‐Kinetic Resolution Process: A Convenient Method for Higher Enantioselectivities and Yields of Chiral Sulfoxide

Abstract: Dedicated to Joe P. Richmond on the occasion of his 60 th birthday.Abstract: A one-pot, titanium-catalyzed tandem sulfoxidation-kinetic resolution process, which combines asymmetric oxidation (at lower temperature) and kinetic resolution (at room temperature), has been developed. Excellent ees (up to > 99.9%) and higher chemical yields of sulfoxides were obtained and the results compared favorable with those from either oxidation or kinetic resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 34 publications
2
24
0
1
Order By: Relevance
“…[34] The process developed by Uemura and co-workers [33,35] has been exploited by Scettri and co-workers (using furyl hydroperoxides as the oxidant) [36] and more recently by Chan and co-workers (using tertbutylhydroperoxide as the oxidant). [37] Specifically, Chan and co-workers described a process in which an initial oxidation at 0 8C (at which temperature the enantioselectivity is optimum) and then at 25 8C (where the kinetic resolution is most efficient) allowed the isolation of sulfoxides in reasonable yields and excellent ee values (65 % and 99.9 % ee in the case of methyl para-tolyl sulfoxide, the best so far published). [37] However, it appears that no significant kinetic resolution in the oxidation of sulfoxides has so far been reported in studies in which chiral vanadium(iv)-Schiff base complexes were used.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…[34] The process developed by Uemura and co-workers [33,35] has been exploited by Scettri and co-workers (using furyl hydroperoxides as the oxidant) [36] and more recently by Chan and co-workers (using tertbutylhydroperoxide as the oxidant). [37] Specifically, Chan and co-workers described a process in which an initial oxidation at 0 8C (at which temperature the enantioselectivity is optimum) and then at 25 8C (where the kinetic resolution is most efficient) allowed the isolation of sulfoxides in reasonable yields and excellent ee values (65 % and 99.9 % ee in the case of methyl para-tolyl sulfoxide, the best so far published). [37] However, it appears that no significant kinetic resolution in the oxidation of sulfoxides has so far been reported in studies in which chiral vanadium(iv)-Schiff base complexes were used.…”
mentioning
confidence: 96%
“…[37] Specifically, Chan and co-workers described a process in which an initial oxidation at 0 8C (at which temperature the enantioselectivity is optimum) and then at 25 8C (where the kinetic resolution is most efficient) allowed the isolation of sulfoxides in reasonable yields and excellent ee values (65 % and 99.9 % ee in the case of methyl para-tolyl sulfoxide, the best so far published). [37] However, it appears that no significant kinetic resolution in the oxidation of sulfoxides has so far been reported in studies in which chiral vanadium(iv)-Schiff base complexes were used. Nevertheless, such an effect has been reported in the case of vanadium-salan systems (selectivity factor S = 7.3 for the resolution of methyl phenyl sulfoxide) when larger amounts of catalyst (5 mol %) were used.…”
mentioning
confidence: 96%
“…[4b,8] Recently Chan developed a one-pot, titanium-catalyzed tandem sulfoxidation and kinetic resolution process, which proceeded at different temperatures and gave extremely high ee values and acceptable yields of chiral sulfoxides. [9] Katsuki found that 10% sulfone was observed in the case of methyl p-nitrophenyl sulfide as substrate during vanadium-catalyzed sulfoxidation;…”
mentioning
confidence: 99%
“…Although a number of approaches using catalytic Ti-complexes of chiral diols have been described in the literature, [19][20][21][22][23][24] many of these cannot be considered truly catalytic, either because they employ only substoichiometric amounts of Ti and diol (up to 0.4 equiv) 21 or give good enantioselectivity not in the enantioselective sulfide oxidation process, but mainly thanks to a kinetic resolution process 25 determined by a concomitant enantioselective overoxidation of the sulfoxide to sulfone. 19,23,[26][27][28][29][30][31][32] In the latter case, although the ee's of sulfoxides are high, this goal is reached with significant reduction of chemical yields, which often do not exceed 50%. Some years ago we described a real catalytical oxidation of sulfides in which the use of 5% mol of a catalyst formed in situ by reacting Ti(i-PrO) 4 , enantiopure 1,2-diphenylethan-1,2-diol (1a), and water gave the optically active sulfoxide in good to high ee's avoiding the overoxidation of sulfoxide to sulfone and kinetic resolution.…”
Section: Introductionmentioning
confidence: 95%